The potential of solar disinfection in combination with bacteriophage biocontrol to reduce the health risks associated with contaminated harvested rainwater - Reyneke, Brandon (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.